Dinâmica da paisagem da microbacia hidrográfica Barreira Bela, Goiás: uma abordagem espaço-temporal - Batista, Jaqueline Gomes (2021)
The Hydrographic Basins constitute important territorial unities of analysis and they are utilized to develop actions of planning and management. In this way, sited on the fluvial plain of the Hydrographic Basin of Araguaia River, the Barreira Bela Microbasin is located in the municipality of Montes Claros of Goiás. Though it is sited in an area of very high vulnerability and it presents high ecological relevance, due to the sensitive and biodiverse areas, like wetlands and Murundu fields, this microbasin has been a target of an intense process of occupancy to the development of agriculture and pasture and the insertion of rural allotments as second residences. These activities can promote degradation, mainly in vulnerable physical environments with complex occupancy, like the second residences that don’t present specific legal supports. Furthermore, the presence of conservation unities around the microbasin is null and the pressure in Cerrado areas due to agricultural frontier expansion has increased. Therefore, this study arises with the general objective of comprehending the physical-natural context and the occupancy history of the Barreira Bela Microbasin, as a way to evaluate its landscape dynamic between 1990 and 2020. The methodology involved bibliographic survey, data collection, organization and refinement, mapping of land use and land cover to the last 30 years, research interviews, measurement of vulnerability to soil loss, geoecological compartmentation, integrated analysis, and planning, based on the precepts of Landscape Geoecology. The results indicate that the remaining Cerrado vegetation is predominant in the microbasin, although the decrease of 31,1% of this class in the last 30 years, converted to anthropic use. Also, it was possible to identify diverse environmental impacts, but one of the main is the occurrence of erosive processes in the study area, and the allotments correspond to the principal factor of influence in this region. Therefore, this study proposes the institution of a conservation unity of sustainable use as a way of plan and manage the Barreira Bela Microbasin, utilizing occupancy tendencies to promote sustainable tourism and conservationist practices of agriculture and pasture.